2011
DOI: 10.1590/s0037-86822011000100029
|View full text |Cite
|
Sign up to set email alerts
|

Scurvy in a patient with AIDS: case report

Abstract: We report the case of a 35-year-old homeless alcoholic and illicit drug user, with AIDS, who was admitted to the emergency unit complaining of asthenia and a weight loss of 30kg over the preceding three months. Clinical and laboratory data confirmed a diagnosis of marasmus, bacterial pneumonia, chorioretinitis caused by Toxoplasma gondii and oral Candida infection. The patient also presented loss of tongue papillae, gingival hypertrophy, perifollicular hyperkeratosis and hemorrhage, coiled, corkscrew-like hair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…38 Gariballa and Foster 26 showed the effect of APR on nutrition status and acute phase proteins serum levels, which were inversely proportional to serum vitamin C levels, suggesting that the APR could be the cause of the observed hypovitaminosis C. Therefore, lower serum vitamin C levels among more severely malnourished patients could be associated with decreased food intake, malabsorption, and increased body nutrient consumption, 39,40 as occurred in malnourished adults with human immunodeficiency virus or spontaneous bacterial peritonitis. 22,23 The present study is in agreement with initial observations of the group, which proposed the original SGA and demonstrated the agreement between this clinical judgment and objective measures of nutrition assessment. In that study, groups differed in relation to body weight, lean and fat weight, and total body measurements of nitrogen and potassium, in addition to serum albumin level and creatinine height index.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…38 Gariballa and Foster 26 showed the effect of APR on nutrition status and acute phase proteins serum levels, which were inversely proportional to serum vitamin C levels, suggesting that the APR could be the cause of the observed hypovitaminosis C. Therefore, lower serum vitamin C levels among more severely malnourished patients could be associated with decreased food intake, malabsorption, and increased body nutrient consumption, 39,40 as occurred in malnourished adults with human immunodeficiency virus or spontaneous bacterial peritonitis. 22,23 The present study is in agreement with initial observations of the group, which proposed the original SGA and demonstrated the agreement between this clinical judgment and objective measures of nutrition assessment. In that study, groups differed in relation to body weight, lean and fat weight, and total body measurements of nitrogen and potassium, in addition to serum albumin level and creatinine height index.…”
Section: Discussionsupporting
confidence: 92%
“…The authors observed a strong association between hypovitaminosis C and the presence of APR . Gariballa and Foster showed the effect of APR on nutrition status and acute phase proteins serum levels, which were inversely proportional to serum vitamin C levels, suggesting that the APR could be the cause of the observed hypovitaminosis C. Therefore, lower serum vitamin C levels among more severely malnourished patients could be associated with decreased food intake, malabsorption, and increased body nutrient consumption, as occurred in malnourished adults with human immunodeficiency virus or spontaneous bacterial peritonitis …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, as often occurs in malnourished, vitamin A-deficient children, who can develop acute anatomical lesions such as xerophthalmia or keratomalacia during measles infection (13), it is also possible that a patient with a chronic vitamin C deficiency could develop the signs and symptoms of scurvy during an acute systemic inflammatory response, as was reported in a hospitalized patient with metastatic renal-cell carcinoma treated with high-dose of interleukin-2 (14). We also described the case of an AIDS patient with increased serum levels of C-reactive protein and multiple opportunistic infections, including neurotoxoplasmosis and acute pneumonia, who developed a full-blown case of scurvy (15). These findings are consistent with reports of an association between low serum vitamin C levels with the presence of an acute-phase response in intensive care units (16).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of scurvy in HIV patients, though uncommon, has been documented in the past. The author's search discovered three such case reports which describe patients who presented with multiple comorbidities ranging in severity from spontaneous bruising, odynophagia and rash to DIC [9][10][11]. In our case, the anemia exhibited by patient, at 5.7 g/dL, is significantly lower than that found in the literature of a similar case, 9.3 g/dL [11].…”
Section: Discussionmentioning
confidence: 45%